Environmental mafia : the enemy is us - O'Leary, Richard, 1949- (Algora Pub., 2003)
The author questions the validity of some (or much) of the agenda of the environmental movement in the U.S., and documents his case with detailed examples of the enormous dangers created by uncontrolled bureaucratic Kafka-esque regulators operating in the name of the higher good. Such regulations and actions sometimes have effects opposite to what was intended, serving neither the environment nor society. As more and more of suburban America is discovering, re-introduced or protected species (bears, deer, geese, etc.) that outstrip the available habitat create safety and sanitation problems for themselves and for humans. O'Leary weaves together a passionate narrative with news articles, studies by the National Center for Public Policy Research and others, and profiles of families whose homes and livelihoods have been destroyed, for no apparent purpose, in the name of environmental protection. Most of the events occurred in the West, but the lessons may apply nationwide. He details the unbearable costs paid by individuals and communities, and in some cases entire state economies, when overblown concern for animals and plants takes precedence over concern for the well-being of mankind. Have the original objectives of well-intentioned citizens been hijacked by others, with different goals in mind? He questions why decisions regarding preservation issues are not made more locally, and observes that increased centralization is robbing citizens of the power of their votes. Topics addressed include property rights, wetlands, the Endangered Species Act, forest fires, urban sprawl, regulatory abuse and violence perpetrated in the name of environmentalism. The book includes documentation sections that back up each chapter with case studies and statistics, and offers lists of Internet links to Pro-Rights Articles and Pro-Rights Organizations.